Where is the future of cardiac lead extraction heading?. (2nd October 2016) - Bongiorni, Maria Grazia; Di Cori, Andrea; Segreti, Luca; Zucchelli, Giulio; Viani, Stefano; Paperini, Luca; Menichetti, Francesca; Coluccia, Giovanni; Soldati, Ezio
ABSTRACT: Introduction: Transvenous lead extraction (TLE) is the gold standard for lead removal. The increasing rate of cardiac implantable electronic device (CIED) implantations and of CIED related complications highlight the importance of transvenous lead extraction . Areas covered: The TLE scenario is constantly changing. Optimizing lead related technology and improving TLE practice across the world are the cornerstones to improving safety and efficacy. We review the state of the art in TLE, focusing on potential future implications and improvements in terms of skills and technologies. Expert commentary: The increased number of extractions will increase the necessity of safe and effective TLE. New technologies, techniques and appropriate training is warranted across the world.